Oscillatory Flow MHD of Jeffrey Fluid with Temperature-Dependent Viscosity (TDV) in a Saturated Porous Channel - Khudair, Wissam Sadiq; Dwail, Hasan Hadi; Mohammed, Hayder Kadim (Iraqi Journal of Science, 2021)
In this research, we studied the impact of Magnetohydrodynamic (MHD) on Jeffrey fluid with porous channel saturated with temperature-dependent viscosity (TDV). It is obtained on the movement of fluid flow equations by using the method of perturbation technique in terms of number Weissenberg ( ) to get clear formulas for the field of velocity. All the solutions of physical parameters of the Reynolds number , Magnetic parameter , Darcy parameter , Peclet number and are discussed under the different values, as shown in the plots.